The “SafeSpace” database of ULF power spectral density and radial diffusion coefficients: dependencies and application to simulations - C. Katsavrias; A. Nasi; I. A. Daglis; I. A. Daglis; S. Aminalragia-Giamini; S. Aminalragia-Giamini; N. Dahmen; C. Papadimitriou; C. Papadimitriou; M. Georgiou; A. Brunet; S. Bourdarie (Annales Geophysicae, 2022)
Radial diffusion has been established as one of the most important mechanisms contributing to both the acceleration and loss of relativistic electrons in the outer radiation belt, as well as to the supply of particles to the inner radiation belt. In the framework of the “SafeSpace” project, we have used 9 years (2011–2019) of multi-point magnetic and electric field measurements from THEMIS A, D and E satellites to create a database of radial diffusion coefficients (DLL) and ultra-low-frequency (ULF) wave power spectral densities (PSDs) spanning an L∗ range from 3 to 8. In this work we investigate the dependence of the DLL on the various solar wind parameters, geomagnetic indices and coupling functions, as well as the L-shell, during the solar cycle 24. Moreover, we discuss the uncertainties introduced on the estimation of DLL time series by the partial azimuthal coverage provided by in situ measurements. Furthermore, we investigate, via a superposed analysis, the dependence of the DLL on solar wind drivers. We show, for the first time to the best of our knowledge, that the interplanetary coronal mass ejection (ICME)-driven disturbances accompanied by high solar wind pressure values combined with intense magnetospheric compression can produce <msubsup>DLLB</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="19pt" height="17pt" class="svg-formula" dspmath="mathimg" md5hash="8c91677e2710d804aad563f1ccb63a3b"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="angeo-40-379-2022-ie00001.svg" width="19pt" height="17pt" src="angeo-40-379-2022-ie00001.png"/></svg:svg> values comparable to or even greater than the ones of <msubsup>DLLE</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="19pt" height="17pt" class="svg-formula" dspmath="mathimg" md5hash="436eaef613984dae2b995cf092da46cf"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="angeo-40-379-2022-ie00002.svg" width="19pt" height="17pt" src="angeo-40-379-2022-ie00002.png"/></svg:svg>. This feature cannot be captured by semi-empirical models and introduces a significant energy dependence on the DLL. Finally, we show the advantages of using DLL time series by means of numerical simulations of relativistic electron fluxes performed with the Salammbô code and significant deviations in the predictions of several semi-empirical models depending on the level of geomagnetic activity and L-shell.